Administration of Internationalization for Living in the ASEAN Community - Tanomsridejchai, Chamaiporn (Rajapark Journal, 2022)
The objectives of this study were to (1) study the administrative problems, (2) investigate the administrative development guidelines, and (3) propose the development guideline model for the administration of internationalization for living in the ASEAN Community. The Internationalization for Living in the ASEAN Community Concept consisting of 3 aspects was applied as the conceptual framework of this study. This study was designated as qualitative research, using documentary research and in-depth interview for qualitative data collection. Upon data processing, interpretation, and analysis, the findings were descriptive presentations together with figures and tables. The findings revealed that 1. The main administrative problem was the government agencies administrated to promote internationalization for living in the ASEAN Community with less emphasis on openness to the world and had no development guideline model of internationalization for living in the ASEAN Community for their implementation. 2. The main development guideline was that government agencies should administer to promote internationalization for living in the ASEAN Community with more emphasis on openness to the world. 3. The development guideline model of internationalization for living in the ASEAN Community based on the Internationalization for Living in the ASEAN Community Concept should comprise three aspects in order of importance: (1) Openness to the World, (2) Inclusion in the World, and (3) Diversity.